Aryl Ketone Mediated Photoinduced Radical Coupling for the Alkylation of Benzazoles Employing Saturated Heterocyclic Compounds - Kamijo, Shin; Kamijo, Kaori; Murafuji, Toshihiro (Synthesis, 2019)
An aryl ketone mediated synthesis of 2-alkylated benzazoles was achieved via radical coupling under photoirradiation starting from saturated heterocycles and 2-sulfonylated benzazoles, such as benzothiazoles, benzoxazole, and benzimidazole. Heterocyclic compounds, including a cyclic ether, azacycles, and tetrahydrothiophene, were applicable, and the benzazole unit was site-selectively installed at the carbon center proximal to the heteroatom. The present transformation takes place at ambient temperature under neutral reaction conditions without the aid of any metallic catalysts or reagents.
Keywords: C–H functionalization; alkylation; benzazoles; photoreaction; aryl ketones